The Importance Of Virtual Presence In Implementing The Quality And Efficiency Of Social Services - Normamatova Mahsuda Nurmamatovna (Global Scientific Publishing, 2025)
This article covers the meaning of the concept of nobility. In an informed society, scientific information is given about virtual images and the impact of virtual reality. Historical progress of the concept of power has been highlighted. The issue of the impact of social life on today's institutions, that is, the developed society, virtual realities, virtual images on the social processes of today is widely described. Today's day youth touched on the obstacles that come to mind when it comes to confronting virtual realities. The question of the impact of the process of turning virtual images into reality on the outlook of people has been studied. Ualualistics has been deeply analyzed as a new philosophical direction, a new paradigm of science. In the article, the concept of creating a healthy social environment is analyzed. In this research work, it is stated that nobility is the being in this capacity and the world of Human Imagination opens the door of wide possibilities
Keywords: virtualuty; knowing; epistemology